PENGEMBANGAN UJI DATA DIGITAL PADA WEBSITE DENGAN DIGITAL FORENSICS - Kusdinar, Asep Budiman (JURNAL GAUNG INFORMATIKA, 2017)
Testing development of data digital is processing the whole of important information is stored in digital of website. This study in order to give understanding of data digital was a specification stored in website. The using method is a digital forensic. The focus of this methods are used to provide direct identification and understanding of information the data digital will be proved. To smooth the use of testing that included also forensic software. This Developing tested can be hoped to complete information, such as: the action of what is being done at the time of website  attacked, any application that is installed, how the website and network systems configured, How to restore the files that have been missing, and finally, how to collect the returned information is missing. This testing Results was collected for using as occurring data digital legality or illegal, so that key questions such as: who, what, when, how, where and why can be answered scientifically.